PENGARUH MOTIVASI BELAJAR SISWA KELAS V TERHADAP PRESTASI BELAJAR MATEMATIKA DI SD NEGERI BEJIREJO KECAMATAN KUNDURAN KABUPATEN BLORA - Ari Indriani (JIPM (Jurnal Ilmiah Pendidikan Matematika), 2016)
The elementary school is the starting point of formal education in Indonesia. In this study used is a public primary schools Bejirejo Kunduran Blora District of the academic year 2013/2014. The sample used is the Elementary School fifth grade students Bejirejo , techniques used in data collection motivation questionnaire. As a precondition test using linearity and significance. While the hypothesis test using t-test. The conclusions of this research is the influence of fifth grade students' motivation to learn mathematics achievement in elementary school Bejirejo.